PEMBELAJARAN ADAPTIF DI PERGURUAN TINGGI PADA MASA PANDEMI COVID-19 - Wahyu Wahyu (CV. ADIBA AISHA AMIRA, 2021)
The Covid-19 virus is endemic and has become the main focus of various countries. The Covid-19 virus has infected millions of people in the world, including Indonesia. Not only the impact in the health sector, but the Covid-19 virus has also had many impacts on the joints of human life. The Covid-19 virus has triggered chaos in various fields of life globally, including the field of education. Gathering activities in order to gain knowledge together, is not recommended to be held. In fact, many countries eliminate face-to-face learning, and replace it with online learning. This policy was implemented to reduce the spread of the Covid-19 virus. In line with these efforts, the campus as a place to forge itself with knowledge, also needs a strategy to help reduce the spread of Covid-19. Efforts to prevent the spread of Covid-19 in the campus environment will be in line with the government's appeal, namely to organize online learning at home. Online learning gives birth to logical consequences, for the perpetrators, both for students and teachers. On the one hand, online learning is an alternative to reduce the possibility of crowding, but online learning also creates challenges to present material in a manner that is able to accommodate scientific demands. Despite the challenges, online learning is definitely expected to foster an attitude of optimism, provide challenges and opportunities to develop innovation, creativity, capacity, personality, and student needs. The solution, lecturers are required to have the ability in the field of learning technology. Another logical consequence is that higher education leaders must be active in optimizing the performance of using online facilities for all lecturers, students, and education staff.